Observation of polar stratospheric clouds over McMurdo (77.85°S, 166.67°E) (2006–2010). Issue 9 (15th May 2014) - Di Liberto, Luca; Cairo, Francesco; Fierli, Federico; Di Donfrancesco, Guido; Viterbini, Maurizio; Deshler, Terry; Snels, Marcel
Abstract Polar stratospheric clouds (PSCs) have been observed in the Antarctic winter from 2006 to 2010 at the Antarctic base of McMurdo Station using a newly developed Rayleigh lidar. Total backscatter ratio and volume depolarization at 532 nm have been measured from 9 km up to 30 km with an average of 90 measurements per winter season. The data set was analyzed in order to evaluate the occurrence of PSCs based on their altitude, seasonal variability, geometrical thickness, and cloud typology derived from observed optical parameters. We have adopted the latest version of the scheme used to classify PSCs detected by the CALIPSO satellite‐based lidar in order to facilitate comparison of ground‐based and satellite‐borne lidars. This allowed us to approximately identify how processes acting at different spatial scales might affect the formation of different PSC particles. The McMurdo lidar observations are dominated by PSC layers during the Antarctic winter. A clear difference between the different type of PSCs classified according to the observed optical parameters and their geometrical thickness was observed. Ice and supercooled ternary solution PSCs are observed predominantly as thin layers, while thicker layers are associated with nitric acid trihydrate particles. The same classification scheme has been adopted to reanalyze the 1995–2001 McMurdo lidar data in order to compare both data sets (1995–2001 versus 2006–2010).